NEW ECONOMY AND EDUCATION OBJECTIVES - Ivan I. Rodionov (Plekhanov Russian University of Economics, 2017)
The article deals with current trends in economy development, conditions of shaping growth points connected with digital goods and services. Emergence of new corporate strategies influences the global education environment. The authors show that in line with today’s changes in economy and society objectives quality criteria of education and professional training are altering drastically, which is connected with the development of people’s creative abilities and finding new ideas in different spheres of activity such as business, social sector, art, science, etc. A potential field of these ideas realization is the use of digital economy.